2007
DOI: 10.1002/oa.873
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, occupation, and whole bone morphology of the pre‐Hispanic Maya coastal population from Xcambó, Yucatan, Mexico

Abstract: The present bioarchaeological study examines the external diaphyseal geometric properties of humeri, radii, femora and tibiae of the Classic period skeletal population of Xcambó , Yucatan, Mexico. The diaphysial proportions are evaluated using a biomechanical approach together with data from the material context and other osteological information. Our intent is to provide new answers to questions concerning lifestyle, domestic labour division and subsistence strategies of this coastal Maya settlement that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
(72 reference statements)
0
29
0
3
Order By: Relevance
“…A shift in lifestyle occurred during the Late Classic. Wanner et al (2007) noted that occupational activities (by means of the analysis of bone robusticity and geometric structure) decreased significantly in the male segment of the population during the Late Classic, when the skeletal evidence indicates a more relaxed, less physically strenuous lifestyle. Women, in turn, maintained the same activity patterns throughout the time span of occupation of the site.…”
Section: Xcambómentioning
confidence: 99%
“…A shift in lifestyle occurred during the Late Classic. Wanner et al (2007) noted that occupational activities (by means of the analysis of bone robusticity and geometric structure) decreased significantly in the male segment of the population during the Late Classic, when the skeletal evidence indicates a more relaxed, less physically strenuous lifestyle. Women, in turn, maintained the same activity patterns throughout the time span of occupation of the site.…”
Section: Xcambómentioning
confidence: 99%
“…Ruff & Hayes, 1983a,b;Ruff, 1987Ruff, , 1992Ruff, , 2000aBridges, 1989Bridges, , 1991Bridges, , 1993Larsen, 1997;Bridges et al, 2000;Ledger et al, 2000;Ruff & Larsen, 2001;Stock & Pfeiffer, 2001, 2004Lazenby, 2002;Holt, 2003;Weiss, 2003;Marchi et al, 2006;Sládek et al, 2006;Wescott, 2006;Carlson et al, 2007;Wanner et al, 2007). It is difficult to relate interpopulation or sex differences to specific activities, particularly for the upper limb due to its multifunctional usage in humans (Bridges, 1989;Stirland, 1993;Ruff & Larsen, 2001;Weiss, 2003), so studies are concerned with general activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Among these were compressed last dorsal vertebrae, arthritic big toes, and knee joint degeneration, which indicate sustained strain on the lower back, toes, and knees, as well as symmetrical muscle markers on the humerus (deltoid) and the radius (biceps), which show symmetrical development of the shoulder and arm muscles consistent with pushing a handstone across a quern (Molleson 1994). Similarly, a study of pre-Hispanic Maya in Mexico showed that females developed bilaterally symmetrical markers on the arms, which the authors attribute to food processing, particularly grinding, compared to males, in whom one dominant arm developed more than the other (Wanner et al 2007).…”
Section: Discussionmentioning
confidence: 90%